Odpowiedzi

Najlepsza Odpowiedź!
2010-02-20T17:04:16+01:00
A) 3(a-2)=3a-6
b) -4(x-y)=-4x+4y
c) -5(-x+1)=5x-5
d) -3a(½-a)=-3/2a+3a²=3a²-3/2a
e)(t-2s-1)razy7=7t-14s-7=-14s+7t-7
f) ½(2a-4b+1)=a-2b+½
g) m(2m+3)=2m²+3m
h) 3p(2r+5p-1)=6pr+15p²-3p=15p²+6pr-3p
i) xy(2x-3y+5)=2x²y-3xy²+5xy
1 4 1
2010-02-20T17:04:26+01:00
A) 3(a-2) = 3a-6
b) -4(x-y) = -4x+4y
c) -5(-x+1) = 5x-5
d) -3a(½-a) = -1,5a+3a^
e) (t-2s-1)*7 = 7t-14s-7
f) ½(2a-4b+1) = a-2b+0,5
g) m(2m+3) = 2m^+3m
h) 3p(2r+5p-1) = 6pr+15p^-3p
i) xy(2x-3y+5) = 2x^y-3xy^+5xy

-------------------------------------------------
^ - do kwadratu (potęgi drugiej)
2010-02-20T17:04:35+01:00
A) 3(a-2)=3a-6
b) -4(x-y)=-4x+4y
c) -5(-x+1)=5x-5
d) -3a(½-a)= -(3/2)a+3a²
e)(t-2s-1)razy7=7t-14s-7
f) ½(2a-4b+1)=a-2b+1/2
g) m(2m+3)=2m²+3m
h) 3p(2r+5p-1)=6pr+15p²-3p
i) xy(2x-3y+5)=2x²y-3xy²+5xy
1 1 1